2014
DOI: 10.1158/1078-0432.ccr-13-2819
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells in Patients with Testicular Germ Cell Tumors

Abstract: Purpose: Germ cell tumors (GCTs) represent the most frequent malignancies among young men, but little is known about circulating tumor cells (CTCs) in these tumors. Considering their heterogeneity, CTCs were investigated using two independent assays targeting germ cell tumor and epithelial cell-specific markers, and results were correlated with disease stage, histology, and serum tumor markers.Experimental Design: CTCs were enriched from peripheral blood (n ¼ 143 patients) and testicular vein blood (TVB, n ¼ 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…In nonmetastatic colorectal cancer (CRC), pre‐operative CTC detection was reported to be an independent prognostic marker (Bork et al., 2015). In testicular germ cell tumors, the presence of CTCs in the PB was shown to be correlated with clinical stage in 41% of CTC‐positive patients with metastasized tumors and in 100% of patients with relapsed and chemotherapy‐refractory disease (Nastaly et al., 2014). Similar results were reported in esophageal cancer (Reeh et al., 2015) and squamous cell carcinoma of the oral cavity (Grover et al., 2014).…”
Section: Markers Of Ctcs In the Pb Or Bm And Clinical Significance Ofmentioning
confidence: 99%
“…In nonmetastatic colorectal cancer (CRC), pre‐operative CTC detection was reported to be an independent prognostic marker (Bork et al., 2015). In testicular germ cell tumors, the presence of CTCs in the PB was shown to be correlated with clinical stage in 41% of CTC‐positive patients with metastasized tumors and in 100% of patients with relapsed and chemotherapy‐refractory disease (Nastaly et al., 2014). Similar results were reported in esophageal cancer (Reeh et al., 2015) and squamous cell carcinoma of the oral cavity (Grover et al., 2014).…”
Section: Markers Of Ctcs In the Pb Or Bm And Clinical Significance Ofmentioning
confidence: 99%
“…In yolk sac tumors and primary extragonadal germ cell tumors, one study reported that the circulating tumor cells are detectable by anti-SALL4 antibody in peripheral blood samples, making this protein a more sensitive marker than α-fetoprotein and glypican-3 107 . In addition, SALL4 is expressed in a majority of malignant rhabdoid tumors (MRTs) 20108109110111 but rarely expressed in epithelioid sarcomas.…”
Section: Sall4 In Cancersmentioning
confidence: 99%
“…Therefore, research is starting to identify the role of circulating tumour cells (CTCs), which are detected in approximately 18% of GCTs. Non-seminomatous tumours associated with CTCs have more aggressive, clinically advanced cancer with increased metastatic potential and disease progression, and are treatment refractory 13. While numerous clinical studies exist on the role and detection of CTCs in metastatic breast, colon and prostate cancer,14–16 little is known in the context of GCTs.…”
Section: Discussionmentioning
confidence: 99%